Validation of Korean Version of the Work Volition Scale. (June 2022) - Kim, Na-Rae; Lee, Ki-Hak
This study aimed to validate a Korean-language version of the Work Volition Scale (WVS). Participants were 453 South Korean adults recruited through a survey panel website. In Phase 1 ( n = 230), the original WVS was translated into Korean. Exploratory factor analysis revealed a three-factor solution (volition, financial constraints, and structural constraints), consistent with the original WVS. In Phase 2 ( n = 223), confirmatory factor analysis supported the goodness of fit of the three-factor structure. Convergent validity tests demonstrated that the Korean WVS was positively correlated ( p < .01) with core self-evaluation and work locus of control and negatively correlated ( p < .01) with the intention to quit employment. In a hierarchical regression analysis, controlling for core self-evaluation and work locus of control, work volition positively predicted job satisfaction ( p < .001). The Korean WVS is a valid assessment tool that can be used by career counselors and researchers working with South Korean adults.